Aplicação de uma rede Fieldbus ao controle de reatores eletrônicos para lâmpadas HPS - Silveira, Roberto Pereira (2004)
This work describes the application of a control fielbus that transmits data over the power lines to control eletronic ballast for high-pressure sodium lamps. Initially, a power line transceiver has been designed, so it is possible to use the installations already assembled to exchange data to control the illumination system in a distributed way. The next step was to implement an eletronic ballast for HPS lamps, in order to test the control fieldbus, without concerns about creating a new ballast topology, but to use a simple topology of an electronic ballast and integrate a control fieldbus into it. Finally, a software application to manage the illumination system was designed, to remotelly control the group of eletronic ballast that constitute the control fieldbus. Experimental results of the eletronic ballast for HPS lamps, the power line transceiver and the software application were shown and discussed.